Thermoplastic polyglycolic acid compounds containing dynamic covalent bonds and methods of making the same

By constructing a dynamic covalent branched/crosslinked structure in polyglycolic acid, the problems of low molecular weight and poor heat resistance of the polymer are solved, realizing the industrial production and application of high molecular weight polyglycolic acid, which has the characteristics of being plastic when heated and strengthening when cooled.

CN122234310APending Publication Date: 2026-06-19CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411870148.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2026-06-19

AI Technical Summary

Technical Problem

In existing polyglycolic acid preparation processes, the polymer has low molecular weight, poor heat resistance, low toughness, slow mass and heat transfer, and is prone to oxidation and yellowing at high temperatures, making it difficult to meet the needs of industrial production and application.

Method used

A dynamic covalent bond chemistry approach was used to construct a thermally reversible branched/crosslinked structure in polyglycolic acid. Thermoplastic polyglycolic acid compounds containing dynamic covalent bonds were prepared by furan-substituted styrene grafting and crosslinking reaction with bisimide compounds, thereby increasing the molecular weight and improving the material properties.

Benefits of technology

It enables polymer plasticization at low temperatures and strengthening at high temperatures, solving the problems of slow mass and heat transfer and oxidation-induced yellowing. The material is easy to industrialize and has good melt flowability and degradability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005195551770000041
    Figure BDA0005195551770000041
  • Figure BDA0005195551770000051
    Figure BDA0005195551770000051
  • Figure BDA0005195551770000061
    Figure BDA0005195551770000061
Patent Text Reader

Abstract

This invention provides a thermoplastic polyglycolic acid compound containing dynamic covalent bonds. The polymer is prepared by thermally reacting polyglycolic acid, furan-substituted styrene grafted monomers, and an initiator in a twin-screw extruder. This polymer is then thermally reacted with a bisimide compound and an antioxidant in a Banbury mixer. This invention provides a novel chain extension route for polyglycolic acid, increasing its molecular weight through a pre-grafting followed by crosslinking approach, thus solving the problems of low molecular weight and poor performance in polyglycolic acid. The material of this invention exhibits the characteristics of being thermoplastic and thermally strengthened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to chain extension technology for polyglycolic acid, and more particularly to a method for synthesizing high molecular weight polyglycolic acid, belonging to the field of polymer material synthesis. Background Technology

[0002] With the rapid development of the polymer materials industry and the widespread use of polymer materials in human life, several problems have arisen. Most traditional polymer materials use non-renewable petroleum resources as raw materials, and the increasing demand for polymer materials is leading to a surge in petroleum consumption, exacerbating global oil shortages. Furthermore, traditional petroleum-based materials are difficult to degrade after use, causing significant damage to the Earth's ecosystems and environment. Therefore, biodegradable polymer materials, which align with the environmentally friendly development of future human society, are becoming a research hotspot as high-tech products and environmentally friendly multifunctional materials. Polyglycolic acid (PGA) is a polymer material with excellent biocompatibility and biodegradability. Compared to traditional polymer materials, PGA can be completely degraded in the human body without the need for special enzymes, and the degradation products can be absorbed and metabolized, ultimately forming carbon dioxide and water. Due to its excellent biocompatibility and biodegradability, PGA and its copolymers are widely used in biodegradable medical surgical sutures, internal fixation devices for fractures, drug-controlled release carriers, and tissue engineering scaffolds.

[0003] Polyglycolic acid (PGA) is mainly prepared by two methods. One is through the condensation polymerization of glycolic acid (direct condensation polymerization is generally the direct dehydration (de-alcoholization) condensation polymerization of glycolic acid (ester). This method does not require the preparation and purification of intermediate products such as dimers, greatly reducing the reaction steps and simplifying the operation. It requires less equipment and has lower requirements for monomer purity. However, its disadvantages are also obvious: due to the small equilibrium constant of the reaction and the difficulty in achieving a high degree of dehydration during polymerization, the molecular weight of the product is often low, typically only a few thousand. The physicochemical properties obtained by this method do not meet the requirements. Furthermore, due to the easy decomposition of PGA, its mechanical strength is far below the requirements for fracture scaffold materials or surgical sutures. In addition, melt condensation polymerization often requires high temperatures, and the product is easily oxidized at high temperatures, leading to discoloration. The other method involves heating and decomposing the glycolic acid condensation polymer to obtain cyclic glycolide. The ring-opening polymerization of glycolide yields high molecular weight PGA with molecular weights ranging from tens of thousands to hundreds of thousands, which can meet the needs of subsequent processing. The ring-opening polymerization of glycolide generally occurs under relatively mild conditions and has some characteristics of living polymerization. Unlike conventional polycondensation reactions, it has fewer side reactions, does not have the problem of equal proportion of raw materials, and is more likely to obtain products with higher molecular weight. At the same time, the ring-opening polymerization of glycolide requires a suitable catalyst to promote it, otherwise the relative molecular weight is difficult to increase.

[0004] The synthesis of polyglycolic acid (PGA) requires high purity of glycolide raw materials. The content of free hydroxyl groups and acids affects the performance of the PGA product. Furthermore, glycolide polymerizes rapidly, and excessively high temperatures can lead to explosive polymerization. During the ring-opening polymerization of glycolide to prepare PGA, due to the material's inherent characteristics, heat and mass transfer are slow. At excessively high temperatures, degradation and easy oxidation and discoloration occur; at low temperatures, polymerization is incomplete, and the melt solidifies, affecting the output. Therefore, to prevent oxidative decomposition and yellowing of the product during polymerization, traditional processes generally employ solid-state polymerization. This method requires sophisticated equipment and presents difficulties in discharging, making industrial production challenging. PGA materials prepared by solid-state reactions generally have low molecular weights and poor performance, making direct production of industrial products difficult. Branching / crosslinking must be used to extend the chain and improve product performance.

[0005] Chinese patent CN107840949A describes a method for copolymerizing a difunctionally end-capped polysiloxane oligomer with glycolide in the presence of an organic solvent under the action of a catalyst to obtain a polyglycolic acid-polysiloxane block copolymer, namely, the organosilicon-modified polyglycolic acid. Compared with polyglycolic acid, this block copolymer has properties such as good flexibility, excellent impact resistance, and good heat resistance. It can be applied in the field of 3D printing technology to quickly and efficiently fabricate complex parts, and is also used in fields such as bioengineering. While copolymerization improves the toughness of polyglycolic acid, the polymer has a small molecular weight and low strength. Patent CN215506720U discloses an apparatus for preparing polyglycolic acid by low-temperature polymerization. The synthesis apparatus includes a melt mixing tank, a static mixer, and a thickening device coupled to the static mixer. Glycol and initiator are first mixed in the melt mixer, and then the mixture enters the static mixer for prepolymerization to obtain glycolic acid prepolymer. The glycolic acid prepolymer is then subjected to final polymerization through the thickening device. Although this apparatus can synthesize high molecular weight polyglycolic acid, the reaction temperature of the thickening device needs to be above 220°C to ensure that the polyglycolic acid is in a fluid state. At high temperatures, polyglycolic acid is prone to oxidative degradation and yellowing, which affects the performance of the product. Patent CN101374883A describes a process where glycolide is first reacted in a prepolymer reactor, and the prepolymer melt is then introduced into a twin-screw agitator to obtain solid pulverized material. This material is further subjected to solid-phase polymerization, and the resulting polymer is then melt-blended with a heat stabilizer and granulated. While this method can effectively produce high-molecular-weight polyglycolic acid with minimal coloring, solid pulverization of polyglycolic acid is difficult, making mass production in the industrial sector challenging. Furthermore, a small amount of yellowing and discoloration can occur during the high-temperature melt-blending process.

[0006] In summary, the current processes for preparing and modifying polyglycolic acid (PGA) mainly have the following problems: (1) Pure PGA products have poor heat resistance and low toughness, requiring modification for industrial application. (2) Simply adding plasticizers and toughening agents to PGA materials cannot fundamentally improve the thermodynamic properties of PGA. (3) Esterification reactions at the end groups of PGA macromolecular chains have low reactivity and poor modification effects. (4) PGA produced by solid-state reactions has a low molecular weight, and due to slow mass and heat transfer, the thermal reaction extrusion temperature is high, resulting in poor melt flowability and a tendency to oxidize and turn yellow. Summary of the Invention

[0007] To address the above shortcomings, this invention provides a method for constructing a thermally reversible branched / crosslinked structure in polyglycolic acid (PGA) through chain extension and dynamic covalent bonding. This imparts upon PGA materials the properties of being plastic when heated and strengthening when cooled, resulting in a high molecular weight thermoplastic PGA compound containing dynamic covalent bonds. This compound has a low processing temperature, good melt flowability, and is easy to degrade, recycle, and industrially produce.

[0008] To achieve the above technical objectives, the technical solution adopted by this invention is as follows:

[0009] The first aspect of this invention aims to provide a thermoplastic polyglycolic acid compound containing dynamic covalent bonds, which is a compound having the general formula I:

[0010]

[0011] Wherein, R1 is selected from -C n H 2n -、 One of them, where n is an integer from 1 to 6;

[0012] R2 is selected from H, methyl, or ethyl.

[0013] Furthermore, R1 is preferably -CH2-, -CH2CH2-, -CH2CH2CH2-, -CH2CH2CH2CH2-, One of them.

[0014] Furthermore, R2 is preferably H.

[0015] Furthermore, the weight-average molecular weight of the thermoplastic polyglycolic acid compound containing dynamic covalent bonds is 1.0 × 10⁻⁶. 5 -2.5×10 5 Preferred size: 1.5×10 5 -2.5×10 5 .

[0016] Furthermore, the melting point of the thermoplastic polyglycolic acid compound containing dynamic covalent bonds is 170-200℃, preferably 175-195℃.

[0017] Furthermore, the melt index of the thermoplastic polyglycolic acid compound containing dynamic covalent bonds is 10-30 g / 10 min, preferably 15-25 g / 10 min.

[0018] Furthermore, the thermoplastic polyglycolic acid compound containing dynamic covalent bonds of the present invention contains a cross-linked structure containing dynamic covalent bonds when the temperature is below 120°C, and the cross-linked structure of dynamic covalent bonds undergoes a reverse depolymerization reaction when the temperature is above 150°C, resulting in the breaking of dynamic covalent bonds. The polyglycolic acid polymer can achieve the characteristics of being plastic (de-crosslinking) when heated and strengthening (crosslinking) when cooled.

[0019] In this invention, the weight-average molecular weight is determined by gel chromatography; the melting point is determined by differential scanning calorimetry; and the melt index is determined by a melt index meter; these are described in detail below.

[0020] The second aspect of this invention aims to provide a method for preparing a thermoplastic polyglycolic acid compound containing dynamic covalent bonds, comprising the following:

[0021] (1) Polyglycolic acid, furan-substituted styrene grafting monomer and initiator were added to a twin-screw extruder for thermal reaction extrusion to prepare furan-substituted styrene grafted polyglycolic acid polymer, and the grafting product was purified.

[0022] The furan-substituted styrene has the structure shown in Formula II:

[0023]

[0024] R2 is selected from H, methyl, or ethyl.

[0025] (2) The grafted product, diimide compound and antioxidant obtained in (1) are thermally reacted in a mixer to prepare a thermoplastic polyglycolic acid compound containing dynamic covalent bonds.

[0026] The diimide compound has the structure shown in Formula III:

[0027]

[0028] Wherein, R1 is selected from -C n H 2n -、 One of them, where n is an integer from 1 to 6.

[0029] Furthermore, the polyglycolic acid mentioned in step (1) is either homemade or purchased, and has a weight-average molecular weight of 0.2 × 10⁻⁶. 5-0.8×10 5 0.4×10 is preferred. 5 -0.8×10 5 .

[0030] Furthermore, the furan-substituted styrene mentioned in step (1) is homemade or purchased, with a chemical purity >99.0%, preferably >99.9%; the amount of furan-substituted styrene added by weight is 1-10% of polyglycolic acid, preferably 2-6%.

[0031] Furthermore, the initiator in step (1) is dicumyl peroxide or 2,5-dimethyl-2,5-bis-(tert-butylperoxide)hexane, preferably dicumyl peroxide; the amount of initiator added is 0.1-5% of polyglycolic acid by weight, preferably 0.5-2.0%.

[0032] Furthermore, step (1) involves a constant-temperature reaction in a twin-screw extruder, with a reaction temperature of 120-170℃, preferably 130-160℃, and a reaction time of 10-100min, preferably 30-60min; the screw shear rate is 20-150rpm / min, preferably 50-100rpm / min.

[0033] The main reaction that occurs in step (1) is shown in the following equation:

[0034]

[0035] Furthermore, the purification in step (1) is carried out by solvent recrystallization, and the solvent used is one of hexoisopropanol, ethyl acetate and acetone, preferably hexoisopropanol.

[0036] Furthermore, in step (1), the grafting rate of furan-substituted styrene grafted with polyglycolic acid is 1-20%, preferably 2-10%.

[0037] The main reaction process in step (2) is shown in the following equation:

[0038]

[0039] Furthermore, the amount of the diimide compound added is 0.5-3% of the polyglycolic acid, preferably 1.0-2.5%, by weight.

[0040] Furthermore, the antioxidant mentioned in step (2) is selected from one of phosphites, alkyl polyphenols and thiobisphenols, preferably triphenyl phosphite, and the amount of antioxidant added is 0.1%-5% of polyglycolic acid, preferably 1-3% by weight.

[0041] Furthermore, in step (2), the reaction temperature of the internal mixer is 150-200℃, preferably 170-190℃; the reaction time is 2-10h, preferably 4-8h.

[0042] Furthermore, the preparation method also includes the step of using high-temperature reactive compounding and extrusion granulation to obtain cross-linked polyglycolic acid resin chips from the thermoplastic polyglycolic acid compound containing dynamic covalent bonds prepared in step (2).

[0043] The technical objective of the third aspect of this invention is to provide applications of thermoplastic polyglycolic acid compounds containing dynamic covalent bonds, which are used in biodegradable medical surgical sutures, internal fixation devices for fractures, controlled-release drug carriers, and tissue engineering scaffolds.

[0044] Compared with existing technologies, the present invention has the following advantages:

[0045] (1) Compared with the prior art, the present invention provides a novel route for polyglycolic acid chain extension. First, furan-substituted styrene is grafted onto polyglycolic acid to obtain a furan-substituted styrene-grafted polyglycolic acid polymer. Then, the furan-substituted styrene-grafted polyglycolic acid polymer is crosslinked with a bisimide compound to obtain a thermoplastic polyglycolic acid polymer containing dynamic covalent bonds. By grafting first and then crosslinking, the molecular weight of polyglycolic acid is increased, and the problems of low molecular weight and poor performance of polyglycolic acid are solved.

[0046] (2) The polyglycolic acid material prepared by the present invention can achieve the characteristics of being plastic (de-crosslinking) when heated and strengthening (crosslinking) when cooled. It solves the problem that polyglycolic acid has a high melting point and that the polymer is prone to rapid oxidation and yellowing when processed at high temperature. It also solves the problem that polyglycolic acid has slow mass and heat transfer, and that the heat transfer of the reaction is not timely, resulting in the solidification of the polymer melt.

[0047] (3) The reaction conditions of this invention are mild, the reaction operation is simple, and it is easy to industrialize.

[0048] Other features and advantages of the present invention will be described in detail in the following detailed description section. Detailed Implementation

[0049] The following non-limiting embodiments are intended to enable those skilled in the art to more fully understand the present invention, but do not limit the invention in any way. Unless otherwise specified, the reagents, materials, and instruments involved in the following embodiments can be obtained through legitimate commercial channels. Unless otherwise specified, the testing and inspection methods involved in the following embodiments are existing testing and inspection methods in the prior art. The following embodiments clearly and completely describe the technical solutions of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. All obvious variations or modifications derived from the present invention still fall within the scope of protection of the present invention.

[0050] The following are the test methods involving performance parameters in the embodiments:

[0051] (1) Grafting rate of furan-substituted styrene-grafted polyethanol polymer was determined by the intensity of characteristic peaks in 1H NMR: the grafting product was dissolved in chloroform, precipitated in methanol, and then extracted with acetone for 24 h to remove unreacted monomers. The grafting efficiency of the polymer was calculated by the peak intensity of the grafted monomers in the 1H NMR spectrum.

[0052] (2) Polymer weight-average molecular weight: Measured by gel permeation chromatography (GPC). The molecular weight of the polyglycolic acid crosslinked polymer was characterized using gel permeation chromatography (GPC Waters 1515 system). Chromatographically pure hexamethylene isopropanol was used as the mobile phase at a flow rate of 1.0 mL / min and a column temperature of 35 °C. Before testing, the sample was dissolved in hexamethylene isopropanol at a concentration of 5 mg / mL, filtered through a 0.22 μm polytetrafluoroethylene (PTFE) membrane, and injected. Calibration was performed using narrow-distribution polystyrene (PS) standards.

[0053] (3) Melting point: Measured using a differential scanning calorimeter (DSC) (DSC 204, Netzsch, Germany). The test conditions were as follows: the sample amount was 5-10 mg. The sample was first heated from room temperature to 250 °C at a heating rate of 10 °C / min and held at isothermal temperature for 5 min to eliminate the thermal history of the sample. Then the sample was rapidly cooled to -20 °C and then heated from -20 °C to 250 °C at a heating rate of 10 °C / min. Nitrogen gas was introduced as a protective gas throughout the test, and the flow rate of nitrogen gas was set to 50 mL / min.

[0054] (4) The melt index is measured by a melt indexer, specifically according to the GB / T3682-2000 standard.

[0055] Example 1

[0056] (1) Replacing styrene with polyglycolic acid and furan as graft monomers Furan-substituted styrene-grafted polyglycolic acid polymers were prepared by thermal reactive extrusion using dicumyl peroxide initiator in a twin-screw extruder. The molecular weight of the polyglycolic acid was 55,000, the amount of dicumyl peroxide added was 0.5 wt% of the polyglycolic acid, the amount of furan-substituted styrene added was 2 wt% of the polyglycolic acid, the reaction temperature in the twin-screw extruder was 130℃, the reaction time was 30 min, and the screw shear rate was 50 rpm / min.

[0057] (2) Furan-substituted styrene-grafted polyglycolic acid compounds, bismaleimide A thermoplastic polyglycolic acid compound containing dynamic covalent bonds was prepared by thermally reacting bismaleimide and the antioxidant triphenyl phosphite in a mixer. The amount of bismaleimide added was 1.0 wt% of polyglycolic acid, the amount of triphenyl phosphite added was 1 wt% of polyglycolic acid, the reaction temperature in the mixer was 170℃, and the reaction time was 4 h.

[0058] Performance characterization: The products of each step were analyzed using the above methods. In step (1), the grafting rate of furan-substituted styrene-grafted polyglycolic acid was 4.5%. The molecular weight of the thermoplastic polyglycolic acid compound containing dynamic covalent bonds prepared in step (2) was 1.8 × 10⁻⁶. 5 The melting point is 178℃ and the melt index is 16g / 10min.

[0059] Example 2

[0060] (1) Replacing styrene with polyglycolic acid and furan as graft monomers Furan-substituted styrene-grafted polyglycolic acid polymers were prepared by thermal reactive extrusion using dicumyl peroxide as an initiator in a twin-screw extruder. The molecular weight of the polyglycolic acid was 60,000, the amount of dicumyl peroxide added was 1 wt% of the polyglycolic acid, the amount of furan-substituted styrene added was 4 wt% of the polyglycolic acid, the reaction temperature in the twin-screw extruder was 150℃, the reaction time was 50 min, and the screw shear rate was 50 rpm / min.

[0061] (2) Furan-substituted styrene-grafted polyglycolic acid polymers, bismaleimide A thermoplastic polyglycolic acid compound containing dynamic covalent bonds was prepared by thermally reacting bismaleimide and the antioxidant triphenyl phosphite in a mixer. The amount of bismaleimide added was 1.5 wt% of polyglycolic acid, the amount of triphenyl phosphite added was 2 wt% of polyglycolic acid, the reaction temperature in the mixer was 180℃, and the reaction time was 6 h.

[0062] Performance characterization: The products of each step were analyzed using the above methods. In step (1), the grafting rate of furan-substituted styrene-grafted polyglycolic acid was 7.8%. The molecular weight of the thermoplastic polyglycolic acid compound containing dynamic covalent bonds prepared in step (2) was 2.1 × 10⁻⁶.5 The melting point is 182℃ and the melt index is 21g / 10min.

[0063] Example 3

[0064] (1) Replacing styrene with polyglycolic acid and furan as graft monomers Furan-substituted styrene-grafted polyglycolic acid polymers were prepared by thermal reactive extrusion using dicumyl peroxide as an initiator in a twin-screw extruder. The molecular weight of the polyglycolic acid was 65,000, the amount of dicumyl peroxide added was 1.5 wt% of the polyglycolic acid, the amount of furan-substituted styrene added was 6 wt% of the polyglycolic acid, the reaction temperature in the twin-screw extruder was 160℃, the reaction time was 60 min, and the screw shear rate was 50 rpm / min.

[0065] (2) Furan-substituted styrene-grafted polyglycolic acid polymers, bismaleimide A thermoplastic polyglycolic acid compound containing dynamic covalent bonds was prepared by thermally reacting bismaleimide and the antioxidant triphenyl phosphite in a mixer. The amount of bismaleimide added was 2 wt% of polyglycolic acid, the amount of triphenyl phosphite added was 3 wt% of polyglycolic acid, the reaction temperature in the mixer was 190℃, and the reaction time was 8 h.

[0066] Performance characterization: The products of each step were analyzed using the above methods. In step (1), the grafting rate of furan-substituted styrene-grafted polyglycolic acid was 5.6%. The molecular weight of the thermoplastic polyglycolic acid compound containing dynamic covalent bonds prepared in step (2) was 2.3 × 10⁻⁶. 5 The melting point is 190℃ and the melt index is 25g / 10min.

[0067] The thermoplastic polyglycolic acid compounds containing dynamic covalent bonds prepared in Examples 1-3 were constructed with thermally reversible branching / crosslinking structures, thereby endowing the materials with the characteristics of branching upon heating (temperature > 150°C) and crosslinking upon cooling (temperature < 120°C), and the polyglycolic acid grafted polymers did not exhibit yellowing.

[0068] Example 4

[0069] (1) Replacing styrene with polyglycolic acid and furan as graft monomers Furan-substituted styrene-grafted polyglycolic acid polymers were prepared by thermal reactive extrusion using dicumyl peroxide initiator in a twin-screw extruder. The molecular weight of the polyglycolic acid was 55,000, the amount of dicumyl peroxide added was 0.5 wt% of the polyglycolic acid, the amount of furan-substituted styrene added was 2 wt% of the polyglycolic acid, the reaction temperature in the twin-screw extruder was 130℃, the reaction time was 30 min, and the screw shear rate was 50 rpm / min.

[0070] (2) Furan-substituted styrene-grafted polyglycolic acid compounds, ethyl bisimide A thermoplastic polyglycolic acid compound containing dynamic covalent bonds was prepared by thermally reacting ethyl bisimide and the antioxidant triphenyl phosphite in a mixer. The amount of ethyl bisimide added was 1.0 wt% of polyglycolic acid, the amount of triphenyl phosphite added was 1 wt% of polyglycolic acid, the reaction temperature in the mixer was 170℃, and the reaction time was 4 h.

[0071] Performance characterization: The products of each step were analyzed using the above methods. In step (1), the grafting rate of furan-substituted styrene-grafted polyglycolic acid was 4.5%. The molecular weight of the thermoplastic polyglycolic acid compound containing dynamic covalent bonds prepared in step (2) was 1.55 × 10⁻⁶. 5 The melting point is 169℃ and the melt index is 12.5g / 10min.

[0072] Comparative Example 1

[0073] Polyglycolic acid polymer (PGA) was obtained by adding glycolide and stannous octoate to a reactor and reacting under nitrogen flow and vacuum conditions at a constant temperature. The polymerization temperature was 165℃, the reaction pressure was 450 kPa, and the reaction time was 60 min. The polymer solidified rapidly. The temperature was then raised to 235℃ until the polymer solid became molten. The melt was then introduced into a thickening device for a thickening reaction to synthesize PGA resin. The thickening reaction temperature was 235℃, the reaction pressure was 50 Pa, and the reaction time was 240 min. Based on the weight of glycolide, stannous octoate accounted for 0.05% of glycolide, and dodecyl alcohol accounted for 0.4% of glycolide.

[0074] Performance characterization: The polyglycolic acid material has a melting point of 173℃ and a molecular weight of 1.68 × 10⁻⁶. 5 The melt index was 13 g / 10 min, and the polymer product showed severe yellowing.

[0075] Comparative Example 2

[0076] (1) Replacing styrene with polyglycolic acid and furan as graft monomers Furan-substituted styrene-grafted polyglycolic acid polymers were prepared by thermal reactive extrusion using dicumyl peroxide as an initiator in a twin-screw extruder. The polyglycolic acid had a molecular weight of 55,000, and the amounts of dicumyl peroxide and furan-substituted styrene added were 0.5 wt% of the polyglycolic acid. The reaction temperature in the twin-screw extruder was 130 °C, the reaction time was 30 min, and the screw shear rate was 50 rpm / min.

[0077] (2) Furan-substituted styrene-grafted polyglycolic acid compounds, bismaleimide A thermoplastic polyglycolic acid compound containing dynamic covalent bonds was prepared by thermally reacting bismaleimide and the antioxidant triphenyl phosphite in a mixer. The amount of bismaleimide added was 0.5 wt% of polyglycolic acid, the amount of triphenyl phosphite added was 1 wt% of polyglycolic acid, the reaction temperature in the mixer was 170℃, and the reaction time was 4 h.

[0078] Performance characterization: The products of each step were analyzed using the above methods. In step (1), the grafting rate of furan-substituted styrene-grafted polyglycolic acid was 1.2%. The molecular weight of the thermoplastic polyglycolic acid compound containing dynamic covalent bonds prepared in step (2) was 1.3 × 10⁻⁶. 5 The melting point is 159℃ and the melt index is 9g / 10min.

Claims

1. A thermoplastic polyglycolic acid compound containing dynamic covalent bonds, characterized in that, It is a compound with the general formula I: Wherein, R1 is selected from -C n H 2n -、 One of them, where n is an integer from 1 to 6; R2 is selected from H, methyl, or ethyl.

2. The thermoplastic polyglycolic acid compound according to claim 1, characterized in that, Its weight-average molecular weight is 1.0 × 10⁻⁶. 5 -2.5×10 5 .

3. The thermoplastic polyglycolic acid compound according to claim 1, characterized in that, Its melting point is 170-200℃.

4. The thermoplastic polyglycolic acid compound according to claim 1, characterized in that, Its melt flow index is 10-30 g / 10 min.

5. The thermoplastic polyglycolic acid compound according to claim 1, characterized in that, The compound contains a cross-linked structure of dynamic covalent bonds when the temperature is below 120°C, and when the temperature is above 150°C, the cross-linked structure of dynamic covalent bonds undergoes reverse depolymerization, and the dynamic covalent bonds break.

6. The method for preparing the thermoplastic polyglycolic acid compound according to claim 1, comprising the following: (1) Polyglycolic acid, furan-substituted styrene grafting monomer and initiator were added to a twin-screw extruder for thermal reaction extrusion to prepare furan-substituted styrene grafted polyglycolic acid polymer, and the grafting product was purified. The furan-substituted styrene has the structure shown in Formula II: in, R2 is selected from H, methyl, or ethyl; (2) The grafted product, diimide compound and antioxidant obtained in (1) are thermally reacted in a mixer to prepare a thermoplastic polyglycolic acid compound containing dynamic covalent bonds. The diimide compound has the structure shown in Formula III: Wherein, R1 is selected from -C n H 2n -、 One of them, where n is an integer from 1 to 6.

7. The preparation method according to claim 6, characterized in that, The weight-average molecular weight of the polyglycolic acid mentioned in step (1) is 0.2 × 10⁻⁶. 5 -0.8×10 5 .

8. The preparation method according to claim 6, characterized in that, In step (1), the amount of furan-substituted styrene added is 1-10% of polyglycolic acid by weight.

9. The preparation method according to claim 6, characterized in that, The initiator mentioned in step (1) is dicumyl peroxide or 2,5-dimethyl-2,5-bis-(tert-butylperoxy)hexane, and the amount of initiator added is 0.1-5% of polyglycolic acid by weight.

10. The preparation method according to claim 6, characterized in that, Step (1) involves a constant-temperature reaction in a twin-screw extruder at a temperature of 120-170℃ for 10-100 min.

11. The preparation method according to claim 6, characterized in that, The purification described in step (1) is carried out by solvent recrystallization, and the solvent used is one of hexamethylene isopropanol, ethyl acetate and acetone.

12. The preparation method according to claim 6, characterized in that, The amount of the diimide compound added is 0.5-3% of the polyglycolic acid by weight.

13. The preparation method according to claim 6, characterized in that, The antioxidant mentioned in step (2) is selected from one of phosphites, alkyl polyphenols and thiobisphenols, and the amount of antioxidant added is 0.1%-5% of polyglycolic acid by weight.

14. The preparation method according to claim 6, characterized in that, In step (2), the reaction temperature in the internal mixer is 150-200℃, and the reaction time is 2-10h.

15. The preparation method according to claim 6, characterized in that, The preparation method further includes the step of using high-temperature reactive compounding and extrusion granulation to obtain cross-linked polyglycolic acid resin chips by using the thermoplastic polyglycolic acid compound containing dynamic covalent bonds prepared in step (2).

16. The application of the thermoplastic polyglycolic acid compound containing dynamic covalent bonds as described in claim 1, for use in biodegradable medical surgical sutures, internal fixation devices for fractures, controlled-release drug carriers, and tissue engineering scaffolds.

Citation Information

Patent Citations

  • Process for producing aliphatic polyester

    CN101374883A

  • Preparation method of organic silicone modified polyglycollide

    CN107840949A

  • Device for preparing polyglycolic acid through low-temperature polymerization

    CN215506720U